Association of Coronary Perivascular Adipose Tissue Inflammation and Drug-Eluting Stent–Induced Coronary Hyperconstricting Responses in Pigs: 18F-Fluorodeoxyglucose Positron Emission Tomography Imaging Study. Issue 9 (September 2017) - Ohyama, Kazuma; Matsumoto, Yasuharu; Amamizu, Hirokazu; Uzuka, Hironori; Nishimiya, Kensuke; Morosawa, Susumu; Hirano, Michinori; Watabe, Hiroshi; Funaki, Yoshihito; Miyata, Satoshi; Takahashi, Jun; Ito, Kenta; et al.
Abstract : Objective—: Although coronary perivascular adipose tissue (PVAT) may play important roles as a source of inflammation, the association of coronary PVAT inflammation and coronary hyperconstricting responses remains to be examined. We addressed this important issue in a porcine model of coronary hyperconstricting responses after drug-eluting stent implantation with 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomographic imaging. Approach and Results—: An everolimus-eluting stent (EES) was randomly implanted in pigs into the left anterior descending or the left circumflex coronary artery while nonstented coronary artery was used as a control. After 1 month, coronary vasoconstricting responses to intracoronary serotonin (10 and 100 μg/kg) were examined by coronary angiography in vivo, followed by in vivo and ex vivo 18 F-FDG positron emission tomographic/computed tomographic imaging. Coronary vasoconstricting responses to serotonin were significantly enhanced at the EES edges compared with the control site ( P <0.01; n=40). Notably, in vivo and ex vivo 18 F-FDG positron emission tomographic/computed tomographic imaging and autoradiography showed enhanced 18 F-FDG uptake and its accumulation in PVAT at the EES edges compared with the control site, respectively (both P <0.05). Furthermore, histological and reverse transcription polymerase chain reaction analysis showed that inflammatory changes of coronary PVAT were significantly enhanced at the EES edges compared with the control site (all P <0.01). Importantly, Rho-kinase expressions (ROCK1/ROCK2) and Rho-kinase activity (phosphorylated myosin phosphatase target subunit-1) at the EES edges were significantly enhanced compared with the control site. Conclusions—: These results indicate for the first time that inflammatory changes of coronary PVAT are associated with drug-eluting stent–induced coronary hyperconstricting responses in pigs in vivo and that 18 F-FDG positron emission tomographic imaging is useful for assessment of coronary PVAT inflammation. Abstract : Supplemental Digital Content is available in the text.